ANALISIS MISKONSEPSI SISWA DALAM MENYELESAIKAN SOAL MISKONSEPSI PADA MATA PELAJARAN BIOLOGI - Hajiriah, Titi Laily; Mursali, Saidil; Dharmawibawa, Iwan Doddy (Bioscientist : Jurnal Ilmiah Biologi, 2019)
Biology is a basic science for studying living things. Basically, some biological content that is contemporary in the learning process is not only in the form of transfer of information and facts from the teacher to students through what they see and what they hear through specific information processing, but requires literal understanding of concepts. Provision of material biological concepts become biased and inherent in one's understanding and cause cognitive conflict that leads to misconceptions. The purpose of this study is to describe the results of the analysis of students' mastery of concepts in solving problems that are considered correct but theoretically wrong. The analysis used in this study was by identifying students' level of understanding in a material and concept. Conclusions from the study that the level of student misconception through its CRI analysis> 2.5 of 30 students, 97% experienced misconception. For this reason, it is necessary to study biological material and be revised by the teacher and students by studying the material and concepts that are correct or bringing in experts in the field of biology.